Non-disjunction of an unusual X chromosome. Issue 4 (August 1976) - Hayata, I; Oshimura, M; Marinello, M J; Bannerman, R M; Sandberg, A A
Abstract : Because of multiple abnormalities in her children, a young mother was investigated and shown to have a 47, XXX chromosome constitution. Additional C group chromosomes without visible centromeric constrictions were found in a number of cells from the peripheral blood, and using C and Q banding techniques these chromosomes were identified as X chromosomes. Analysis of the banding karyotypes of 300 cells revealed that the acentric X chromosomes had the ability to replicate and that this replication was associated with non-disjunction leading to aneuploid cells. Even though cultured skin cells did not have acentric or extra chromosomes in addition to the triple-X, examination of buccal mucosa cells for the presence of X-bodies suggested that the phenomenon of non-disjunction was present in the epithelial cells of the patient. In addition to the X without a visible centromeric constriction, either acentric D or E chromosomes were found. The data suggest that a functional defect in the cells per se is responsible for the appearance of the acentric chromosomes.